Más allá del formato. Una mediateca virtual como propuesta de emprendimiento cultural para creadores emergentes (2015)
This article explores the theoretical approaches to the cultureas concept, its links with globalization, and the culturalentrepreneurship development in countries like Colombia.From the cultural entrepreneurship perspective, the definitionsrelated to theoretical propositions to the potential applicationsbased on the use of media and communication technologiesare considered. A virtual multimedia library is the outcomeof these relationships; the products in the design, advertisingand marketing areas by students is the main supply to builda digital repository, a platform for exposition, spreading andcultural entrepreneurship for emerging artists in the near futurethat also make memory around communication possible to beconstructed.